THE NORMATIVE STUDY ON THE AREA/SPACE STRUCTURE POLICY OF STATE BORDER IN MALUKU PROVINCE - Kennedy, Posma Sariguna Johnson; L.Tobing, Suzanna Josephine; Heatubun, Adolf; Lumbantoruan, Rutman (Fundamental Management Journal, 2018)
The purpose of this paper is to review the management of border area functions in accordance with the mandate of Law no. 43 of 2008 on National Territory. This study is based on the Master Plan for State Boundary Management, and the Priority Location Master Plan, which is a common reference for all stakeholders. In this research, as the methodology used is the review literature using qualitative normative method. This means to review the regulations related to the arrangement of spatial function of State Border Area in Maluku Province. Spatial Planning of Border Areas in Maluku Province aims: To create a state defense and security function that ensures the integrity of the territorial sovereignty and order which borders are the State of Timor Leste and the State of Australia; Effective protected areas to protect biodiversity, protected forests, and coastal borders including in small outer islands (PPKT) and; Make border areas that are self-reliant and competitive.Keywords: State Border Area, National Strategic Activities Center (PKSN), Priority Location (Lokpri), Spatial Plan (RTRW)